Evaluating Population Genetic Structure and Demographic History of Quercus spinosa (Fagaceae) Based on Specific Length Amplified Fragment Sequencing - Ju, Miao-Miao; Feng, Li; Yang, Jia; Yang, Yan-Ci; Chen, Xiao-Dan; Zhao, Gui-Fang (Frontiers in Genetics, 2019)
Effectively identifying the genetic structure and related factors of a species can facilitate understanding the evolutionary history of the species. Phylogeographic patterns and genetic data are essential in investigating the species historical processes and diversification that response to environmental, climatic and geological influences. In this study, Specific Length Amplified Fragment Sequencing (SLAF-seq) data and ecological niche models (ENMs) are combined to identify the genetic structure and demographic modeling of Quercus spinosa, and evaluate the impacts of historical range shifts, climatic variation and landscape factors on this species. The population topology and genetic divergence of the Cenozoic were inferred by a site frequency spectrum based composite-likelihood approach which is a novel strategy for maximizing the utility of linked SLAF markers. The overall genetic structure using model-based and model-free clustering methods was consistently identified as two geographically distinct genetic clusters. A deep divergence between two natural lineages (i.e., a western Himalaya-Hengduan Mountains lineage and an eastern Qin-ling Mountains lineage) was observed. The demographic modeling and Niche reconstruction indicated that the two groups were diverged in the late Miocene and then presented as two distinct genetic lineages. With the Quaternary glacial climate fluctuation, two groups had continuous asymmetrical secondary contact and gene exchange in the Sichuan Basin during the last glacial maximum. Besides, a significant relationship between genetic distance and geography in all individuals was identified by the Mantel test. Overall, this study 1) contributes to a better understanding of the role played by Quaternary climatic fluctuation in the present-day distributions of Q.spinosa; 2) provides a comprehensive view of the genome-wide variation of sclerophyllous forests in ecological adaptive evolution; 3) indicates that dispersal limitation and ecological divergence contribute to the genome-wide differentiation of Q.spinosa, which supports a hypothesis that complex geography and climatic changes strongly influence the evolutionary origin and history of the species.